Etika Pendidik Dalam Surat Al-A’raf Ayat 199 Kajian Ilmu Pendidikan Islam - Wahidah, Evita Yuliatul; Mukhtar, Aceng Musyaffa (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
The Qur'an is the holy book of Islam, whose content is indisputable and serves as a guide for humanity to navigate life in this world. It is inherently a book of education. Consequently, the Qur'an encompasses various terminologies related to education, including aspects concerning the educator. Numerous verses in the Qur'an outline how a teacher should conduct themselves, as exemplified in Surah Al-A'raf, verse 199. This study aims to describe the educator's ethics as derived from Surah Al-A'raf, verse 199, from the perspective of Islamic Education Science. This research adopts a library research methodology, involving an examination of the interpretations by Islamic scholars of Surah Al-A'raf, verse 199, and written sources on educator ethics as articulated by experts or scholars. It is qualitative research with a descriptive method focusing on content analysis of the Qur'anic interpretation of Surah Al-A'raf, verse 199, and the content of related texts. Based on the findings, it can be concluded that the ethics of an educator contained in Surah Al-A'raf, verse 199, include being forgiving, preventing wrongdoing, and avoiding ignorant people. The ethics of an educator, as derived from the study of Surah Al-A'raf, verse 199 in Islamic Education Science, imply that an educator should be gentle, compassionate, and forgiving. This means that being an educator requires a high level of patience in teaching. An educator should be able to guide and set a positive example for their students and, simultaneously, prevent and shield them from negative influences. Turning away from ignorant people signifies that educators must discern and select the attitudes or traits of students that need further development or education. Keywords : Educator Ethics, Islamic Education Science